KETERKAITAN ANTARA LEADER MEMBER EXCHANGE, PERCEIVED ORGANIZATIONAL SUPPORT, KOMITMEN AFEKTIF DAN KINERJA STUDI PADA KARYAWAN PT ADIKENCANA MAHKOTABUANA KEBAKKRAMAT KARANGANYAR - Asrori (Jurnal Ilmiah Cano Ekonomos, 2017)
The purpose of this research was to investigates and analysis correlation between leader member exchange, perceived organizational support, affective commitment and performance. The research focuses on employee performance PT Adikencana Mahkotabuana Kebakkramat Karanganyar. The study unitilizes probability sampling method and simple random sampling technique with 201 sample from 1.250 population. By using structural equational modeling analysis, the findings indicate that: (1) Leader member exchange and affective commitment positive interaction on employee performance with c.r value 3.198 ( 2) Leader member exchange and perceived organizational support positive interaction on affective commitment of employee with c.r value 4.294 and 7.503 ( 3) Perceived organizational support not significant on employee performance with c.r value 0,587 ( 4) Leader member exchange positive interaction on employee performance with mediated affective commitment regression weight indirect effect 0,107. Management PT Adikencana Mahkotabuana Kebakkramat to increase of employee performance with focus leader member exchange, perceived organizational support and affective commitment.